2012
DOI: 10.1021/ef3009234
|View full text |Cite
|
Sign up to set email alerts
|

Coconut-Shell-Based Porous Carbons with a Tunable Micro/Mesopore Ratio for High-Performance Supercapacitors

Abstract: Granular micro/mesoporous carbon with a ratio of mesopore to total pore volume (V meso/V total) greater than 75% was prepared using coconut shells as a precursor by a one-step thermal treatment, i.e., combined pyrolysis and steam activation process. The process variables, such as final activation temperature, time, and water flow rate were studied. The N2 adsorption isotherms of the samples were of type IV, indicating mesoporous characteristics. The mesoporosity of the resultant porous carbons prepared by this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
132
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(135 citation statements)
references
References 56 publications
(73 reference statements)
2
132
0
1
Order By: Relevance
“…The weight loss above 400 °C was due to gradual decomposition of lignin. [25] A 32% char yield was observed at 700 °C which is much higher than that of other bioderived carbons. For example, jute rope showed a yield of 11%, while kapok fibers produced carbon with a 20% yield.…”
Section: Resultsmentioning
confidence: 86%
“…The weight loss above 400 °C was due to gradual decomposition of lignin. [25] A 32% char yield was observed at 700 °C which is much higher than that of other bioderived carbons. For example, jute rope showed a yield of 11%, while kapok fibers produced carbon with a 20% yield.…”
Section: Resultsmentioning
confidence: 86%
“…Lignin pyrolyzes steadily over a wide temperature range, and the weaker peak between 430 and 500 °C may represent the decomposition of lignin. Lignin contributes predominantly to the formation of char [40,41]; about 21% char yield was observed at 700 °C. The SEM images in Figure 2 revealed the effect of chemical activation and pyrolysis on the morphology We analyzed the pyrolysis behavior of orange peel precursor under a nitrogen atmosphere using thermogravimetric analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, varieties of natural biomass have been utilized as starting materials to prepare porous carbon materials for supercapacitor [18][19][20]. It was reported that willow catkins activated by KOH present large threedimensional interconnected micrometer-level pores composed of sheet-like primary particles [20].…”
Section: Introductionmentioning
confidence: 99%